Uncovered Interest Parity in its Precise Form of ASEAN-5 Currencies: A Markov Switching Approach - Paul, Hiew Kar Hin (2017)
This research examines the Uncovered Interest Parity relationship of ASEAN-5 currencies, which are Singapore Dollar, Malaysia Ringgit, Indonesia Rupiah, Thai Baht and Philippines Peso, against US dollar. As different from previous studies, this paper model Uncovered Interest Parity in its precise form rather than the commonly used approximate form along with the potential arbitrage direction. Two different data frequencies, which are monthly and weekly, were used for the sample period of 2005 to 2015 for better comparison. Markov-Switching Model is applied to test the effect of different volatility regimes on the efficiency of Uncovered Interest Parity along with the standard OLS model. The general findings suggest that Inward arbitrage opportunity exists within the Singapore Dollar, Indonesia Rupiah, Thai Baht and Philippines Peso. There is also evidence of a UIP violation reversal when low volatility regime switch into high volatility regime. The Markov-Switching Model results also provide evidence of structural break within the period of mid-2008 to mid-2010 that caused by sub-prime crisis and subsequently the US Federal Reserve Bank’s near zero interest rate policy.